2019
DOI: 10.1162/asep_a_00700
|View full text |Cite
|
Sign up to set email alerts
|

Geographical and Strategic Factors in Chinese Foreign Direct Investment in Europe

Abstract: Recently, the volume of Chinese FDI made in Europe has reached the level of European FDI in China (now constrained by restrictions and risks). It equaled the level of FDI made by Chinese firms in the United States before they began to decline in the last two years. The Chinese economic presence in Europe is divided into three parts in terms of volume, destination, and type of acquisition: The heart of Europe is made up of the three major destinations (Germany, UK, France), where more capital-intensive investme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 4 publications
0
8
0
Order By: Relevance
“…Similarly, Abbas and Mosallamy (2016) using a panel data model found that resources, market openness, human capital, infrastructure and political stability are significant determinants of F.D.I. Likewise, Richet (2019) reveals that countries with smaller market opportunities receive less direct investment.…”
Section: Literature Reviewmentioning
confidence: 94%
“…Similarly, Abbas and Mosallamy (2016) using a panel data model found that resources, market openness, human capital, infrastructure and political stability are significant determinants of F.D.I. Likewise, Richet (2019) reveals that countries with smaller market opportunities receive less direct investment.…”
Section: Literature Reviewmentioning
confidence: 94%
“…Second, given the demonstrated importance of economic integration for FDI (Bandelj, 2010 ; Bitzenis, 2016 ; Kekic, 2005 ), disruptions in Balkan countries’ EU accession progress will be detrimental to FDI inflows from other European origin countries. Third, although China remains only a minor player in this region at the time of writing, its future role could be monumental (Richet, 2019 ). China’s global Belt and Road Initiative features a major Balkan corridor passing through many of these countries, and its 16 + 1 diplomatic outreach toward CEE imply that its leaders seek a “backdoor” to European markets for Chinese MNEs.…”
Section: Suggestions For Policy and Further Researchmentioning
confidence: 99%
“…The major destinations in Europe are Germany, the United Kingdom and France, where major capital investments are made, followed by other European as well as Western Balkan countries. The Western Balkan countries receive less investment than the most developed countries, mainly due to smaller market opportunities, but in no case can they be considered as small amounts because they contribute significantly to the economic development of these countries (Richet, 2019). China has very good bilateral relations with the EU and therefore investing in those countries may provide even better access to Chinese companies in the future (Jia, 2015;Parenti & Chen, 2019).…”
Section: економикаmentioning
confidence: 99%